Active control for mid-span connection of a deployable tensegrity footbridge. (1st April 2016) - Veuve, Nicolas; Dalil Safaei, Seif; Smith, Ian F.C.
Highlights: A control methodology for a deployable tensegrity footbridge is presented. A symmetric topology of the bridge halves is well-suited for mid-span connection. A combination of stochastic search and simulation computes control commands. Real-time measurement of the structure helps finding successful control commands. Abstract: Tensegrity structures are spatial self-stressed pin-jointed structures where compression components (struts) are surrounded by tension elements. This paper describes a near full-scale deployable tensegrity footbridge that deploys from both sides and connects at mid-span. Two topologies that differ in terms of symmetry of elements and paths of continuous cables are compared. Although both topologies behave similarly with respect to serviceability criteria, there is a significant difference in behavior during deployment. A two-stage control methodology for the connection of both halves of the footbridge is presented. The control methodology determines active cable length changes based on computational control and measurement of the response of the structure during deployment. Both halves are successfully connected at the end of deployment.